ANALISIS METODE PEMBELAJARAN DALAM KITAB TAFSIR AL-MISBAH VOLUME 15 KARYA M. QURAISH SHIHAB - Pahrurraji, Pahrurraji (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
This study proposes an analysis of learning methods in the Book of Tafsir Al-Misbah volume 15 by M. Quraish Shihab. The formulation of the problem in this study is how the learning method is in the Book of Tafsir Al-Misbah volume 15 by M. Quraish Shihab. This study aims to determine the learning method in the Book of Tafsir Al-Misbah volume 15 by M. Quraish Shihab. This type of research is library research, namely research on library/literature materials related to research problems. Based on the results of the research conducted, there are several analyzes of learning methods in the Book of Tafsir Al-Misbah volume 15 by M. Quraish Shihab namely the objectives of the learning method, the material of the learning method, the learning method, as an educator both parents and teachers must be able to teach these learning methods by well and by using good strategies and methods to students so that students will be able to correctly understand the things they have to do and the things they have to leave behind.